(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
This paper discusses the ideas and personal views of S. Othman Kelantan in his novel Juara and examines how U-Wei Shaari, the director of the film Jogho, responds to the original ideas in the novel. The paper focuses on three methods in the adaptation from novel to film as suggested by Klein and Parker, namely: a) literal translation, in which the original work is faithfully kept to; b) re-interpretation, which retains the basic structure of the narrative but in some circumstances deconstructs the original work; and c) using the original work only as raw material to produce a new work. The study finds that U - Wei Haji Shaari’s version is a re-interpretation maintaining the idea of the original novel and the basic structure of the narrative. However, both creative works contain a message for the Malays of Kelantan and Pattani who share the same language, culture and religion but are separated by political borders. Keywords: adaptation, adaptation methods, Klein and Parker, re-interpretation, Kelantan Malays, Pattani Malays